T Cells Promote Bronchial Epithelial Cell Secretion of Matrix Metalloproteinase‐9 via a C‐C Chemokine Receptor Type 2 Pathway: Implications for Chronic Lung Allograft Dysfunction. Issue 6 (23rd January 2017) - Pain, M.; Royer, P.‐J.; Loy, J.; Girardeau, A.; Tissot, A.; Lacoste, P.; Roux, A.; Reynaud‐Gaubert, M.; Kessler, R.; Mussot, S.; Dromer, C.; Brugière, O.; et al.
Abstract : Chronic lung allograft dysfunction (CLAD) is the major limitation of long‐term survival after lung transplantation. CLAD manifests as bronchiolitis obliterans syndrome (BOS) or restrictive allograft syndrome (RAS). Alloimmune reactions and epithelial‐to‐mesenchymal transition have been suggested in BOS. However, little is known regarding the role of allogenicity in epithelial cell differentiation. Primary human bronchial epithelial cells (BECs) were treated with activated T cells in the presence or absence of transforming growth factor (TGF)‐β. The expression of epithelial and mesenchymal markers was investigated. The secretion of inflammatory cytokines and matrix metalloproteinase (MMP)‐9 was measured in culture supernatants and in plasma from lung transplant recipients (LTRs): 49 stable, 29 with BOS, and 16 with RAS. We demonstrated that C‐C motif chemokine 2 secreted by T cells supports TGF‐β–induced MMP‐9 production by BECs after binding to C‐C chemokine receptor type 2. Longitudinal investigation in LTRs revealed a rise in plasma MMP‐9 before CLAD onset. Multivariate analysis showed that plasma MMP‐9 was independently associated with BOS (odds ratio [OR] = 6.19, p = 0.002) or RAS (OR = 3.9, p = 0.024) and predicted the occurrence of CLAD 12 months before the functional diagnosis. Thus, immune cells support airway remodeling through the production of MMP‐9. Plasma MMP‐9 is a potential predictive biomarker of CLAD. Abstract : The authors investigate the production of matrix metalloproteinase‐9 by primary bronchial epithelial cells after interaction with activated T cells and show that plasma matrix metalloproteinase‐9 can serve as a predictor of chronic lung allograft dysfunction 12 months before clinical diagnosis.